Blonde Venus y el género cinematográfico de la mujer caída (Andamios, Revista de Investigación Social, 2011)
This article analyzes some problems related to the representation of the fallen woman in the Blonde Venus film, regarding to the fact that its unconventional treatment caused many setbacks with censorship, and this conflict allows to observe closely the representation mechanisms in the Hollywood’s classic cinema. In spite of the film reassumed the western dichotomy between the images of the mother and the prostitute (Mary versus Eve), Marlene Dietrich’s character incarnates both roles at once, generating ambiguities and contradictions that de-stabilize the moralist discourses on the fallen woman and on the housewife; such discourses meet a peak by the end of the nineteenth century, to be later reassumed by the cinema.
Keywords: Fallen woman; representation; classic Hollywood cinema; gender; family